KOLABORASI PEMERINTAH PUSAT DAN DAERAH DALAM PENGEMBANGAN KAWASAN EKONOMI KHUSUS (KEK) DI INDONESIA - Silsila Asri; Yahya Krisnawansyah (LPPM STISIP IMAM BONJOL, 2022)
The development of special economic areas (KEK) of local governments collaborates with the central government and private parties. The development of a region into a special economic area requires a real planning and action. Supported by regional autonomy demanding the role of local governments in realizing the SNR, it also requires collaboration with the central government in addition to the large role of the private sector in economic activity. Government and private cooperation with Indonesia's infrastructure development model involves the private sector, local government, central government in a synergy with their respective roles and functions that allow for a clear division of positions, duties and responsibilities set out within the legal framework of legal in carrying out development projects. The strategy that can be pursued by local governments in realizing SNR is to build collaboration with private parties and central government in public private partnership schemes.